2018
DOI: 10.1001/jamadermatol.2018.1408
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Gel Treatment vs Placebo for Facial Angiofibromas in Patients With Tuberous Sclerosis Complex

Abstract: IMPORTANCE Most patients with tuberous sclerosis complex (TSC), an autosomal-dominant disorder that is caused by the constitutive activation of mammalian target of rapamycin, experience disfigurement caused by skin lesions involving facial angiofibromas. Many have been left untreated because of a lack of therapeutic options that are less invasive than surgery or laser treatment. OBJECTIVE To confirm the efficacy and safety of sirolimus gel, 0.2%, for treatment of patients with angiofibromas and/or skin lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 30 publications
3
84
0
2
Order By: Relevance
“…for FA associated with TSC using the Dermatology Life Quality Index (DLQI) and Children's DLQI (CDLQI). They reported that the total scores on the DLQI and CDLQI after 12 weeks of treatment did not differ markedly between the sirolimus gel group and the placebo group 7 . Similar findings were reported in previous studies analyzing the QOL improvement of patients with topical mTOR inhibitors for FA associated with TSC using the DLQI and CDLQI 10,11 .…”
Section: Patient Characteristics Treatment Efficacy and Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…for FA associated with TSC using the Dermatology Life Quality Index (DLQI) and Children's DLQI (CDLQI). They reported that the total scores on the DLQI and CDLQI after 12 weeks of treatment did not differ markedly between the sirolimus gel group and the placebo group 7 . Similar findings were reported in previous studies analyzing the QOL improvement of patients with topical mTOR inhibitors for FA associated with TSC using the DLQI and CDLQI 10,11 .…”
Section: Patient Characteristics Treatment Efficacy and Adverse Eventsmentioning
confidence: 99%
“…The conditions of the patients after three months of treatment with sirolimus gel were classified into three categories according to the criteria shown in Table 1: "improved," "unchanged," and "aggravated." 7 Adverse events were investigated using the CTCAE v5.0-JCOG (National Cancer Institute, Bethesda, MD, USA). This study was approved by the institutional review board of JR Tokyo General Hospital (No.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wataya-Kaneda et al reported phase 2 and 3 randomized clinical trials of topical sirolimus treatment with a sirolimus gel formulation in TSC patients and showed signi cant reductions in the size and color of the FAs associated with TSC 6,7 . In Japan, sirolimus gel was approved for the treatment of TSC skin lesions in 2018.…”
Section: Introductionmentioning
confidence: 99%